2014
DOI: 10.1016/j.ijsu.2014.08.377
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in elderly patients. A comparison between gastric banding and sleeve gastrectomy with five years of follow up

Abstract: Bariatric surgery is safe and effective to reach obesity related comorbidities resolution among elderly obese patients. Both LAGB and LSG determine a weight loss lesser than observed in a standard bariatric population. In this study LSG is significantly less cost effective than LAGB. Larger studies with longer follow up are however needed to evaluate the real impact of bariatric surgery on weight loss, resolution of comorbidities and improvement of quality of life in elderly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Percentage excess weight loss at a mean of 33 months post-surgery was 56.7 % for super-obese elderly patients in our study, which is very similar to the 59.3 % recorded at a similar time interval after laparoscopic gastric bypass in all elderly patients [9], and better than the 28.8 % recently recorded for morbidly obese elderly patients undergoing sleeve gastrectomy [10]. It has been reported that super-super-obese patients have significantly lesser %EWL than morbidly obese [3]; but in our comparison of super-obese with morbidly obese elderly patients, there was no difference in %EWL between the two groups.…”
Section: Resultssupporting
confidence: 87%
“…Percentage excess weight loss at a mean of 33 months post-surgery was 56.7 % for super-obese elderly patients in our study, which is very similar to the 59.3 % recorded at a similar time interval after laparoscopic gastric bypass in all elderly patients [9], and better than the 28.8 % recently recorded for morbidly obese elderly patients undergoing sleeve gastrectomy [10]. It has been reported that super-super-obese patients have significantly lesser %EWL than morbidly obese [3]; but in our comparison of super-obese with morbidly obese elderly patients, there was no difference in %EWL between the two groups.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, no revision surgery was performed for insufficient weight loss. Previous studies also reported clinically significant excess weight loss and improvement in quality of life after bariatric surgery in elderly patients, but most of these effects were not as significant as those observed in younger patients [16,26,28,37,39]. However, most of these studies have only examined short-term weight-loss (< 1 year of follow-up after surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Because many studies consider patients aged 460 years as elderly, it is difficult to interpret the current literature regarding elderly patients undergoing bariatric surgery. These different definitions of the elderly patient introduces selection bias and limits the conclusions that can be drawn regarding the super-obese geriatric population [19][20][21].…”
Section: Discussionmentioning
confidence: 99%